Controlled ultrasonic interventions through the human skull - Wilson, Matthew G.; Riis, Thomas S.; Kubanek, Jan (Frontiers in Human Neuroscience, 2024)
Transcranial focused ultrasound enables precise and noninvasive manipulations of deep brain circuits in humans, promising to provide safe and effective treatments of various neurological and mental health conditions. Ultrasound focused to deep brain targets can be used to modulate neural activity directly or localize the release of psychoactive drugs. However, these applications have been impeded by a key barrier-the human skull, which attenuates ultrasound strongly and unpredictably. To address this issue, we have developed an ultrasound-based approach that directly measures and compensates for the ultrasound attenuation by the skull. No additional skull imaging, simulations, assumptions, or free parameters are necessary; the method measures the attenuation directly by emitting a pulse of ultrasound from an array on one side of the head and measuring with an array on the opposite side. We show that the correction enables effective stimulation of finger nerves and effective release of propofol from nanoparticle carriers in an ex vivo human skull, while neither application was effective without correction. Moreover, the effects show the expected dose-response relationship and targeting specificity. This article highlights the need for precise control of ultrasound intensity within the skull and provides a direct and practical approach for addressing this lingering barrier.